Quorum Sensing System Affects the Plant Growth Promotion Traits of Serratia fonticola GS2 - Jung, Byung Kwon; Ibal, Jerald Conrad; Pham, Huy Quang; Kim, Min-Chul; Park, Gun-Seok; Hong, Sung-Jun; Jo, Hyung Woo; Park, Chang Eon; Choi, Seung-Dae; Jung, Yeongyun; Tagele, Setu Bazie; Shin, Jae-Ho (Frontiers in Microbiology, 2020)
Quorum sensing (QS) enables bacteria to organize gene expression programs, thereby coordinating collective behaviors. It involves the production, release, and population-wide detection of extracellular signaling molecules. The cellular processes regulated by QS in bacteria are diverse and may be used in mutualistic coordination or in response to changing environmental conditions. Here, we focused on the influence of the QS-dependent genes of our model bacterial strain Serratia fonticola GS2 on potential plant growth promoting (PGP) activities including indole-3-acetic acid (IAA) production, 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity, and biofilm formation. Based on genomic and phenotypic experimental data we identified and investigated the function of QS genes in the genome of the model strain. Our gene deletion study confirmed the biological functionality of the QS auto-inducer (gloI) and receptor (gloR) on potential PGP activities of GS2. A transcriptomic approach was also undertaken to understand the role of QS genes in regulation of genes primarily involved in PGP activities (IAA, ACC deaminase activity, and biofilm formation). Both transcriptomic and phenotypic data revealed that the QS-deletion mutants had considerably less PGP activities, as compared to the wild type. In addition, in vivo plant experiments showed that plants treated with GS2 had significantly higher growth rates than plants treated with the QS-deletion mutants. Overall, our results showed how QS-dependent genes regulate the potential PGP activities of GS2. This information may be helpful in understanding the relationship between QS-dependent genes and the PGP activity of bacteria, which aid in the production of practical bio-fertilizers for plant growth promotion.